Measuring Feeling Safety as a Moderating Effect of Worker Skills on Team Performance During the Covid-19 Pandemic - Suryo Wibowo; Yustinus Yuniarto (Universitas Bunda Mulia, 2021)
The unclear end of the current Covid-19 pandemic signals concern not only for workers but also for organizations. This condition makes company income non-existent so that inevitably the company makes efficiency, one of which is reducing workers. One of the methods for carrying out this action for the company can be determined by the aspect of the work skills of the workers so that they can still make the maximum contribution to the company. On the one hand, workers feel a signal of insecurity in working for the future. In a broader context, this feeling safety also refers to the availability of safety aspect equipment provided by the organization for workers. This study aims to measure the role of feeling safety as a moderator of worker skills on worker performance. This research is a quantitative study using the Partial Least Square - Structural Equation Modeling (PLS-SEM) model. By using SMART PLS 3.0 and 99 respondents who are workers from various fields of work and types of companies in Indonesia, this study explains that feeling safety at work can not be a moderating effect between skills and work performance. In addition, this study succeeded in explaining that feeling safety actually affects work performance in the company. The next result explains that work skills affects the work performance of workers. In order to survive in the midst of difficult conditions, the work skills of workers is an important key and to be able to improve organizational performance, a series of forms of training for workers need to be held by the organization. On the other hand, to increase awareness of safety aspects in work, routine delivery of information on safety aspects needs to be carried out continuously.